Managing Arabic Language Learning Using The Blended Learning Models: Can It Improve Student Interest? - Febriani, Nailin Nabilah; Thohir, Muhammad; Wida, Sabilla Setia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The blended learning method emerged as an answer to the weaknesses of face-to-face and online learning. With this, the researchers were moved to discuss the student's interest in learning Arabic using the blended learning method. This research uses qualitative research and descriptive approaches. The methods used in data collection include three things: interviews, questionnaires, and observations. Data sources were obtained from students and Arabic language teachers, and research was conducted in MAN 2 Malang City by being analyzed using data condensation, data presentation, and conclusion. The result is that implementing blended learning can increase students' interest in learning Arabic lessons and find out the supporting and inhibiting factors for the performance of combined learning models in Arabic language learning. This study aims to determine students' interest in learning Arabic using blended learning as a reference for teachers in the future.